CCRL1/ACKR4 is expressed in key thymic microenvironments but is dispensable for T lymphopoiesis at steady state in adult mice. Issue 2 (16th January 2015) - Lucas, Beth; White, Andrea J.; Ulvmar, Maria H.; Nibbs, Robert J. B.; Sitnik, Katarzyna M.; Agace, William W.; Jenkinson, William E.; Anderson, Graham; Rot, Antal
<x xml:space="preserve">Abstract</x> Thymus colonisation and thymocyte positioning are regulated by interactions between CCR7 and CCR9, and their respective ligands, CCL19/CCL21 and CCL25. The ligands of CCR7 and CCR9 also interact with the atypical receptor CCRL1 (also known as ACKR4), which is expressed in the thymus and has recently been reported to play an important role in normal αβT‐cell development. Here, we show that CCRL1 is expressed within the thymic cortex, predominantly by MHC‐IIlowCD40− cortical thymic epithelial cells and at the subcapsular zone by a population of podoplanin+ thymic epithelial cells in mice. Interestingly, CCRL1 is also expressed by stromal cells which surround the pericytes of vessels at the corticomedullary junction, the site for progenitor cell entry and mature thymocyte egress from the thymus. We show that CCRL1 suppresses thymocyte progenitor entry into the thymus, however, the thymus size and cellularity are the same in adult WT and CCRL1−/− mice. Moreover, CCRL1−/− mice have no major perturbations in T‐cell populations at different stages of thymic differentiation and development, and have a similar rate of thymocyte migration into the blood. Collectively, our findings argue against a major role for CCRL1 in normal thymus development and function.